(untitled) (JS (JURNAL SEKOLAH), 2026)
Abstract: Pancasila holds an important position as the foundation of the state and a source of values that underlies the implementation of national education in Indonesia. Amid globalization and the rapid development of the digital era, education is expected not only to enhance students’ academic competencies but also to foster citizenship character that reflects the nation’s core values. This article aims to analyze the axiology of Pancasila as a reflection of educational philosophy in fostering citizenship character among elementary school students. This study employed a library research method with a qualitative descriptive approach. Data were collected from various sources, including books, journal articles, and official documents relevant to axiology, educational philosophy, Pancasila, and citizenship character. The findings indicate that the axiology of Pancasila serves as a value foundation in education that guides character formation through the internalization of religious, humanitarian, unity, democratic, and social justice values. The implementation of these values can be carried out through classroom learning, school culture, contextual learning, teacher role modeling, and the involvement of families and communities. In the digital era, the axiology of Pancasila remains relevant as a moral and social foundation that guides students in responding to various social and technological challenges. Therefore, strengthening the axiology of Pancasila in elementary education is a strategic effort to develop students’ citizenship character so that they become responsible, ethical, and nationally minded citizens. Keyword: Pancasila axiology, educational philosophy, citizenship character, elementary education, character education. Abstrak: Pancasila memiliki kedudukan penting sebagai dasar negara sekaligus sumber nilai yang menjadi landasan penyelenggaraan pendidikan nasional. Di tengah perkembangan globalisasi dan era digital, pendidikan tidak hanya dituntut untuk mengembangkan kemampuan akademik peserta didik, tetapi juga membentuk karakter kewarganegaraan yang mencerminkan nilai-nilai luhur bangsa. Artikel ini bertujuan untuk menganalisis aksiologi Pancasila sebagai refleksi filsafat pendidikan dalam menumbuhkan karakter kewarganegaraan siswa sekolah dasar. Penelitian ini menggunakan metode kajian pustaka (library research) dengan pendekatan deskriptif kualitatif. Data diperoleh melalui berbagai sumber pustaka berupa buku, artikel jurnal, dan dokumen resmi yang relevan dengan aksiologi, filsafat pendidikan, Pancasila, dan karakter kewarganegaraan. Hasil kajian menunjukkan bahwa aksiologi Pancasila memiliki peran sebagai landasan nilai dalam pendidikan yang mengarahkan pembentukan karakter peserta didik melalui internalisasi nilai religiusitas, kemanusiaan, persatuan, demokrasi, dan keadilan sosial. Implementasi nilai-nilai tersebut dapat dilakukan melalui pembelajaran, budaya sekolah, keteladanan guru, pembelajaran kontekstual, serta keterlibatan keluarga dan masyarakat. Di era digital, aksiologi Pancasila tetap relevan sebagai fondasi moral dan sosial dalam membimbing peserta didik menghadapi berbagai tantangan perubahan sosial dan teknologi. Dengan demikian, penguatan aksiologi Pancasila dalam pendidikan dasar menjadi langkah strategis dalam membentuk karakter kewarganegaraan siswa yang berintegritas, bertanggung jawab, dan berkomitmen terhadap nilai-nilai kebangsaan. Kata Kunci: aksiologi Pancasila, filsafat pendidikan, karakter kewarganegaraan, pendidikan dasar, pendidikan karakter